A63 EUS-GUIDED BILIARY DRAINAGE FOR DECOMPRESSION OF MALIGNANT BILIARY OBSTRUCTION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th March 2019) - Miller, C; Barkun, A N; Martel, M; Chen, Y
Abstract: Background: Endoscopic ultrasound (EUS)-guided biliary drainage (BD) is increasingly used for malignant distal biliary obstruction, yet its safety and efficacy are not well established, especially as a first-line modality when compared to endoscopic retrograde cholangiopancreatography (ERCP). Aims: To conduct a systematic review and meta-analysis to determine the safety and efficacy of EUS-BD for the treatment of malignant biliary obstruction. Methods: The literature was systematically searched through September 2018, querying Embase, MEDLINE, CENTRAL and ISI Web of Knowledge. All abstracts and fully-published randomized controlled trials (RCTs) that compared EUS-BD to another modality for decompression of malignant biliary obstruction were included. A meta-analysis was conducted with results reported as risk ratios (RRs) with 95% confidence intervals (CIs) using a random effects model. The primary outcome of interest was comparative risk of reintervention. Prespecified subgroup analysis by comparator was performed. Results: Initial search yielded 1264 papers. Following review, 8 trials (2 abstracts) are included that randomized 406 patients to either EUS-BD as primary treatment vs. ERCP (3 studies, n=220) or EUS-BD as rescue therapy vs. percutaneous transhepatic biliary drainage (PTBD) (3 trials, n=132) or surgery (2 trials, n=52). Overall, EUS-BD is associated with a decreased risk for reintervention (RR, 0.48; 95% CI, 0.32–0.71). On subgroup analysis, reintervention rates also favoured EUS-BD over ERCP (RR, 0.40; 95% CI, 0.23–0.71) and PTBD (RR, 0.49, 95% CI, 0.28–0.88). In addition, compared to ERCP, EUS-BD is associated with decreased risk for stent dysfunction (RR, 0.52; 95% CI 0.29–0.94), tumour in/overgrowth (RR, 0.18; 95% CI, 0.05–0.69) and post-procedure pancreatitis (RR, 0.12; 95% CI, 0.01–0.97). There is decreased risk of adverse events compared to PTBD (RR, 0.59; 95% CI, 0.39–0.87) but no difference was observed overall. No difference was noted in technical/clinical success overall or in the subgroup analyses. No significant heterogeneity or publication bias was noted. Conclusions: In a meta-analysis of RCTs, EUS-BD is associated with similar technical/clinical success as other drainage modalities including ERCP. It is, however, associated with decreased risk for reintervention, stent tumor in/overgrowth, and post-procedure pancreatitis, suggesting a promising role as a first-line modality for malignant distal biliary obstruction. Funding Agencies: None